Study of the Evaporation Process in the Spray Zone of a Mechanical Draft Wet Cooling Tower - Dany Iman Santoso; Bambang Antoko; Prabowo Prabowo; Djatmiko Ichsani (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
The evaporation process in the nozzle spray system of a cooling tower was the main object of study in order to determine its performance. This process involves liquid water in small size, usually at the droplet level. At this level, parameters that affect the droplet size, such as capacity, air velocity in the chamber, water pressure at the nozzle, atmospheric temperature, etc., influence the process of heat and mass transfer. In this study, capacity and fan rotation were varied to obtain a graph showing the evaporation. Radius, velocity, mass and temperature graphs and rate graphs were obtained from mathematical modeling of the governing equations. From the results it appears that evaporation occurs at a capacity of 6 liter per minute and above, but this requires further proof of the evaporation process along with the height of the tower, which will be the subject of a future study.